Effects of interactions between the parasitoids Tetrastichus howardi and Cotesia flavipes on biological control of sugar cane borer Diatraea saccharalis: insights from an experimental study - Oliveira, Juliana S.; Diniz, Alexandre J. F. [UNESP]; Reigada, Carolina (Schweizerbart, 2024)
Diatraea saccharalis (Lepidoptera: Crambidae), the sugarcane borer, is the main pest of sugarcane crops, direct and indirectly causing damage to the sugar-ethanol agribusiness. Cotesia flavipes (Hymenoptera: Braconidae) is the most relevant biological control agent that suppresses sugarcane stalk borer populations. However, since C. flavipes parasitizes 14 to 43% of the sugarcane stalk larvae in the field, the resort of other biological control agents is valued. In this context, a biological control alternative is featured by the association of C. flavipes with Tetrastichus howardi (Hymenoptera: Eulophidae), a generalist parasitoid that preferably attacks D. saccharalis pupal stage. To evaluate whether this association can increase the effectiveness of borer control throughout the sugarcane harvest cycles, the parasitism rates of D. sacch-aralis larvae and/or pupae were compared in four experimental scenarios: (i) interaction of C. flavipes with D. saccharalis larvae, (ii) interaction of T. howardi with D. saccharalis pupae, (iii) interaction of C. flavipes and T. howardi with D. sac-charalis larvae, and (iv) interaction of C. flavipes and T. howardi with larvae and pupae of D. saccharalis. The interactions between both parasitoid species and sugarcane borer were given in a system of cages under controlled conditions. Despite the reports of D. saccharalis larvae being attacked by T. howardi in some studies, this investigation did not evidence the wasp parasitizing sugarcane borer larvae. Thus, the simultaneous use of two parasitoid species did not interfere on the performance of C. flavipes when there were only D. saccharalis larvae in experimental cages. Nevertheless, when larvae and pupae of sugarcane borer were present, the simultaneous occurrence of larvae and pupae of borer, and both parasitoid species, exhibited additive effects on the host mortality rate.
Keywords: Additive mortality; biological control; Braconidae; Eulophidae; overlapping generations; Sugarcane borer